THE PERFORMANCE OF FAMILY PLANNING COUNSELORS TOWARDS DEPARTMENT OF POPULATION CONTROL AND FAMILY PLANNING IN MAKASSAR CIT - Thahier, Rohana; Haris, Rima Melati (Jurnal Administrasi Negara, 2019)
Family planning counsellors are an important factor in carrying out family planning programs, but the performance of family planning counsellors towards Department of Control of Population and Family Planning in Makassar City are still not optimal. Based on these problems, this research aims to determine and analyse the performance of family planning counsellors at the Department of Control of Population and Family Planning in Makassar. The research method used in this research is descriptive quality method. Data collection methods used in this research are interviews, document review and observation. Meanwhile, data collection instruments used in this research are interview guidelines, guidelines for reviewing documents and observation guidelines. Moreover, data analysis techniques used in this research are conducted by means of data reduction, data presentation, conclusions drawing and verification. After that, the validity of the data is tested by using the triangulation technique. The results of this research indicated that the overall performance of family planning counsellors was in a good category but there were still several indicators that need to be improved to maximize the performance of family planning counselors.